Time and frequency nexus among public debt, exchange rate, inflation, monetary policy rate and economic growth in Ghana - Owusu Junior, Peterson (Elsevier, 2025)
The debate about the influence of public debt on an economy has gained long-standing attention among policy-makers, regulators and academic scholars. The excessive expansion of Ghana’s public debt to GDP demands a fresh insight into the macroeconomic variables that are connected to economic growth. This study utilised wavelet techniques to investigate the nexus and effect of public debt, exchange rate, inflation rate, and monetary policy rate on economic growth in Ghana using monthly data from 2000 to 2022. Diks and Panchenko (2006) was used as a battery test for the wavelet results. We found a significant negative correlation between public debt and GDP at both short- and long-term frequencies, though there was no notable connection in the medium term. The causality analysis suggests a possibility of bidirectional causality between GDP and public debt in both the short and medium term. Interestingly, the COVID-19 pandemic had minimal impact on this relationship when comparing the pre-pandemic and during-pandemic periods. The only observed coherence (negative) between monetary policy and GDP occurred between 2000 and 2003, at low and medium frequencies. The WMCC results depicted that no variable was seen to lead or lag during the pandemic period however, GDP (exchange rate) reacted to shocks first (last) in the short run (long run) prior to the pandemic. The result of this research is crucial for policy implementation. The GDP-public debt negative nexus offers strong evidence for the government to make determined efforts to reduce external borrowing. The positive coherence of exchange rates and the public debt offers a strong incentive to the monetary authorities to make determined efforts to stop the rapid rise of exchange rates.
Keywords: COVID-19 pandemic; Economic growth; Exchange rate; Public debt; Monetary policy rate; Inflation rate; SDG-17: Partnerships for the goals